Gender Diversity, Corporate Governance, Financial Performance, and corporate value: Lesson from Indonesian Public Company Before Covid-19 - Setiawanta, Yulita (Universitas Dian Nuswantoro Semarang, 2022)
This study attempted to uncover the role of gender in corporate leadership, corporate governance, and financial performance and its effect on creating corporate value. Companies listed on the Indonesia Stock Exchange with this research's 2009-2018 observation period. Samples were taken with strict criteria to find companies in the best food and beverage category and were obtained 50 observation data for ten years. The research considered this type of company directly related to basic human life and worthy of investment. The results showed that gender diversity and EPS could not create Corporate Value. Managerial Ownership, PBV, and DER were significantly able to develop Corporate Value. The results of this study were enjoyable to be examined from the perspective of the situation of organizational behavior and financial performance of public companies and be informed to potential investors or interested parties, especially the situation in Indonesia, the country with the fourth-largest population in the world or 3.51% of the total human population.Keywords: Gender Diversity, Managerial Ownerships, Earning per Share, Price to Book Value, Debt to Equity Ratio